STRUCTURAL-FUNCTIONAL MODEL: KEY ACTORS AND MECHANISMS OF INTERACTION - Valery V. Bespalov (Статистика и экономика)
The article deﬁnes the role of the restructuring of the management system, wherean important aspect highlighted in theprocess of building a structural-functionalmodel of restructuring. Main approachesto the construction of models for the restructuring of the management system: astrategic approach, cybernetic approach,project approach. Formulated necessaryand sufﬁcient conditions for the creation and implementation of structural-functional model of restructuring. An algorithmof constructing the structural-functionalmodel of restructuring of the management system.